Evaluation of the Utilization of Food Support Schemes in Urban Poor Population in Rishikesh, Uttarakhand - Sharma, Divita; Khapre, Meenakshi; Kaushal, Pawna (National Journal of Community Medicine, 2021)
The rapid emergence of rural agglomeration in urban areas has resulted in increased number of slum areas, which are highly vulnerable to food insecurity. There is a dearth of literature and evidence on food insecurity in such areas. The present study was thus aimed to determine the prevalence of food insecurity at household level in urban poor settlements of Rishikesh and the extent of utilization of food support schemes. Methodology: It was a mixed method study carried out in the households of urban poor region of Rishikesh. Each respondent was selected from a set inclusion criteria and interviewed using a questionnaire for sociodemographic factors and food insecurity through Household Food Insecurity Access Scale. Results: Out of 100 households that were assessed, 52% were food insecure, out of which 20% were severely food insecure and 4% mildly food insecure. A significant association was seen between prevalence of food insecurity and lower socioeconomic status (SES). Conclusion: More than half of the households were found to be food insecure during COVID-19 lockdown in spite of fair coverage of various food support schemes. There should be more research regarding the persistent issue of food insecurity even after a large coverage of the food support schemes.